The Economic Impact of Climate Change in Italy - Fragomeni, Fabio; Rizzo, Rosalba (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: In addition to being a threat to human health and life, climate change is an economic threat. The objectives of this article are to reflect on the consequences of global warming on Italian economic dynamics and to report on the costs and benefits of adapting strategies in a specific area at risk in Italy, particularly coastal erosion/flooding.Research Design & Methods: The article places particular emphasis on the analysis of the situation in this area to be used for proper economic evaluation.Findings: While the climate change does not end at level of the economy, reflecting on prospective economic losses can help to understand climate risks. The research is limited by a lack of analysis involving other coastal areas at risk in Italy.Implications / Recommendations: The strategies adapted in these areas at risk pose new interesting questions about the climate risks.Contribution: The study examines global warming and highlights the strategy of adaptation as a process for reducing our vulnerability to the harmful effects of climate change.